2022
DOI: 10.1021/acsomega.2c05343
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Graphene–TiO2–SnO2 Ternary Nanocomposites for High-Performance Asymmetric Supercapacitors

Abstract: Ternary nanocomposites synergistically combine the material characteristics of three materials, altering the desired charge storage properties such as electrical conductivity, redox states, and surface area. Therefore, to improve the energy synergistic of SnO2, TiO2, and three-dimensional graphene, herein, we report a facile hydrothermal technique to synthesize a ternary nanocomposite of three-dimensional graphene–tin oxide–titanium dioxide (3DG–SnO2–TiO2). The synthesized ternary nanocomposite was characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Hence, this structure increased the capacitive property of the electrode by accelerating the electrolyte ion transport and reducing the polarization of the electrode surface. 40…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, this structure increased the capacitive property of the electrode by accelerating the electrolyte ion transport and reducing the polarization of the electrode surface. 40…”
Section: Resultsmentioning
confidence: 99%
“…Hence, this structure increased the capacitive property of the electrode by accelerating the electrolyte ion transport and reducing the polarization of the electrode surface. 40 GCD curves obtained from the three-electrode studies of the NVO/MXene composite electrode were evaluated to determine the practical cycling performance. The GCD performance of the NVO and MXene electrodes is compiled in the ESI (S5b and S6b).…”
Section: Electrochemical Properties Of the Nvo/mxene Compositementioning
confidence: 99%
“…In 3 M KOH solution, the EIS was carried out using a three‐electrode setup throughout a frequency range of 100 kHz–10 mHz at 10 mV. A supercapacitor's Nyquist plot is usually composed of three sections: a Warburg resistance at low frequency, a series resistance at high frequency, and a charge transfer resistance at mid frequency 70–75 . Figure 11A shows the Nyquist plots obtained for P3MT, P3MT/NiO, P3MT/NiS, and P3MT/NiO/NiS nanocomposites electrode materials.…”
Section: Resultsmentioning
confidence: 99%
“…A supercapacitor's Nyquist plot is usually composed of three sections: a Warburg resistance at low frequency, a series resistance at high frequency, and a charge transfer resistance at mid frequency. [70][71][72][73][74][75] Figure 11A shows the Nyquist plots obtained for P3MT, P3MT/NiO, P3MT/ NiS, and P3MT/NiO/NiS nanocomposites electrode materials. The EIS data were fitted using ZSimpWin based on the equivalent electrical circuit.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…According to Yin and co-workers [ 22 ], the ternary nanocomposite exhibited superior durability and reproducibility than binary composites. Zamiri et al, reported that the incorporation of 3DG into the SnO 2 –TiO 2 binary nanocomposite increased its surface area and decrease size compared to the single and binary composite [ 23 ]. This results a high adsorption of substrates on the catalyst surface and increase the catalytic processes.…”
Section: Introductionmentioning
confidence: 99%